Cytotoxicity of monomers, plasticizer and degradation by-products released from dental hard chairside reline resins - Lima Chaves, Carolina de Andrade [UNESP]; Machado, Ana Lucia [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Elsevier B.V., 2010)
Objectives. The aim of this study was to evaluate the cytotoxic effect of the monomers isobutyl methacrylate (IBMA) and 1,6-hexanediol dimethacrylate (1,6-HDMA), the plasticizer di-n-butyl phthalate (DBP), and the degradation by-products methacrylic acid (MA) and benzoic acid (BA) on L929 cells. Based on previous investigations on the release of these compounds from hard chairside reline resins, a range of concentrations (mu mol/L) were selected for the cytotoxicity tests (IBMA, 5.491406.57; 1,6-HDMA, 1.2239.32; DBP, 1.12143.8; MA, 9.07581; BA, 3.19409).Methods. Cytotoxic effects were assessed using MTT and 3H-thymidine assays after the cells had been exposed to the test compounds at the given concentrations for 24h. Cytotoxicity was rated based on cell viability relative to controls (cells exposed to medium without test substances).Results. DNA synthesis activity was inhibited by all compounds. Mitochondrial dehydrogenase activity decreased in cells treated with monomers, plasticizer and MA by-product, whereas no cytotoxic effect was observed on contact with BA at the majority of concentrations tested. The ranges of suppression for 3H-thymidine assay were: IBMA, 2595%; 1,6-HDMA, 9598%; DBP, 4098%; MA, 9799%; BA, 5471%. For MTT assay, the ranges of suppression were: IBMA, 096%; 1,6-HDMA, 2689%; DBP, 1780%; MA, 5266%; BA, 027%. The 3H-thymidine assay was more sensitive than the MTT assay.Significance. This study evaluated the cytotoxicity of a wide range of concentrations of monomers (IBMA and 1,6-HDMA), plasticizer (DBP) and degradation by-products (MA and BA), including those expected to be released from hard chairside reline resins. The differences observed in the cytotoxicity of these compounds, along with other properties, may assist the dental practitioners in the selection of reline materials with improved service life performance and low risk of adverse reactions in patients who wear relined dentures.
Keywords: Acrylic resins; Cytotoxicity; Monomer; Plasticizer; Degradation products; Fibroblasts